First language use in Arabic language classrooms : teacher perspective - Mohamad Azrien, M.A.; Shukeri, M.; Mohd Alwee, Y.; Zamri, G. (2014)
The use of the target language has long been considered an important principle of second language (L2) instruction. Previous research has attempted to quantify the amount of the first language (L1) used in the classroom and has explored the purposes or functions of teachers' ‘lapses’ into their students' L1. The purpose of this qualitative study is to explore the teachers’ attitudes towards the use of Bahasa Indonesia in Arabic language classroom. Data was collected based on the interviews of the teachers. The respondents of this study were two experienced teachers who have more than 15 years of teaching experience. The findings indicated that teachers prefer using Arabic language itself in Arabic language classroom. The Direct Method was applied as teaching strategies. The use of student’s first language is prohibited in or outside the classroom. As a result, students are able to speak Arabic without any sense of shame and fear. Because of the prohibition of using L1 in the school campus, the institution is able to educate its students to master Arabic language.